Outdoor air pollution and mosaic loss of chromosome Y in older men from the Cardiovascular Health Study. (July 2018) - Wong, Jason Y.Y.; Margolis, Helene G.; Machiela, Mitchell; Zhou, Weiyin; Odden, Michelle C.; Psaty, Bruce M.; Robbins, John; Jones, Rena R.; Rotter, Jerome I.; Chanock, Stephen J.; Rothman, Nathaniel; Lan, Qing; et al.
Abstract: Background: Mosaic loss of chromosome Y (mLOY) can occur in a fraction of cells as men age, which is potentially linked to increased mortality risk. Smoking is related to mLOY; however, the contribution of air pollution is unclear. Objective: We investigated whether exposure to outdoor air pollution, age, and smoking were associated with mLOY. Methods: We analyzed baseline (1989–1993) blood samples from 933 men ≥65 years of age from the prospective Cardiovascular Health Study. Particulate matter ≤10 μm (PM10 ), carbon monoxide, nitrogen dioxide, sulfur dioxide, and ozone data were obtained from the U.S. EPA Aerometric Information Retrieval System for the year prior to baseline. Inverse-distance weighted air monitor data were used to estimate each participants' monthly residential exposure. mLOY was detected with standard methods using signal intensity (median log-R ratio (mLRR)) of the male-specific chromosome Y regions from Illumina array data. Linear regression models were used to evaluate relations between mean exposure in the prior year, age, smoking and continuous mLRR. Results: Increased PM10 was associated with mLOY, namely decreased mLRR (p-trend = 0.03). Compared with the lowest tertile (≤28.5 μg/m 3 ), the middle (28.5–31.0 μg/m 3 ; β = −0.0044, p = 0.09) and highest (≥31 μg/m 3 ; β = −0.0054, p = 0.04) tertiles had decreased mLRR, adjusted for age, clinic, race/cohort, smoking status and pack-years. Additionally, increasing age (β = −0.00035, p = 0.06) and smoking pack-years (β = −0.00011, p = 1.4E−3) were associated with decreased mLRR, adjusted for each other and race/cohort. No significant associations were found for other pollutants. Conclusions: PM10 may increase leukocyte mLOY, a marker of genomic instability. The sample size was modest and replication is warranted. Highlights: Investigated whether outdoor air pollution was related to loss of Chromosome Y in leukocytes, a genomic instability marker. Analyzed baseline blood samples from 933 U.S. men ≥65 years of age from the prospective Cardiovascular Health Study. Subject-specific exposure to particulate matter ≤10 μm (PM10 ) and other pollutants were derived from U.S. EPA data. Increased exposure to PM10 from outdoor air pollution may contribute to loss of Chromosome Y in leukocytes.